Viability of Italian ryegrass (Lolium multiflorum) seeds under application of synthetic auxin herbicides - Dal’Pizol Novello, Bruna; Orsolin da Silva, Diecson Ruy; Cuchi, Marina Luiza; Alba da Silva, Álvaro Andre (Revista Ceres, 2022)
Italian ryegrass (Lolium multiflorum) is one of the main weeds in the wheat crop, and the application of synthetic auxin herbicides has the potential to reduce seed viability, therefore, restricting the input into the seed bank. The objective was to evaluate the effects of synthetic auxin herbicides applied at different growth stages on germination, emergence and initial growth of Italian ryegrass. The herbicides treatments were 2,4-D, 2,4-D+picloram and dicamba applied at four different growth stages of Italian ryegrass in field and seeds quality evaluated in laboratory and greenhouse studies. In both studies, the herbicides did not reduce Italian ryegrass seed germination or emergence regardless of application growth stages. Under laboratory conditions, the application of synthetic auxin herbicides increased vigor and germination speed by up to 64 and 47%, respectively, applied in advanced growth stages. The greenhouse test evidenced an increase in vigor by the herbicides application, but only 2,4-D increased the emergence speed and plant dry matter when applied in early plant stage. The synthetic auxin herbicides do not alter germination or emergence. Progenies treated with herbicides had greater seed vigor.